Land uses shifts the abundance and structure of soil biota and soil chemical traits in tropical ecosystem, Apodi Plateau, Brazil - Gondim, Joaquim Emanuel Fernandes; de Souza, Tancredo Augusto Feitosa; Portela, Jeane Cruz; Santos, Djail; Batista, Rafael Oliveira; Nascimento, Gislaine dos Santos; da Silva, Lucas Jónatan Rodrigues [UNESP]; Laurindo, Lídia Klestadt; Dias, Pollyana Mona Soares (Springer Nature, 2024)
Land uses may shift soil biota community composition, and soil chemical traits. Our aims were to assess if the land uses may influence the soil biota community composition and soil chemical traits; if there are differences into soil biota biomass as influenced by land uses; and what are the plant-soil feedback among the land uses, soil biota, and soil chemical traits. We have collected soil samples and extracted soil biota individuals from four different land uses (e.g., natural ecosystem, conventional farming system, agroecological farming system, and fruticulture). Our results have revealed that land uses have influenced soil biota abundance (from 59.0 to 210.12 ind. trap− 1 in the natural ecosystem and fruticulture system, respectively), richness (from 6.5 to 10.5 in the fruticulture system, and natural ecosystem, respectively), diversity (from 1.01 to 1.75 in the conventional farming system, and natural ecosystem, respectively), dominance (from 0.52 to 0.71 in the natural ecosystem, and conventional farming system, respectively), and its biomass. The studied land uses have decreased the soil organic carbon when compared with the natural ecosystem (5.75 g kg− 1). SOC, soil pH, Olsen’s available P, Mg2+, K+, and Na+ were the main factors contributing to the variance of the samples accounting for 78% of the data variance. The results of our study highlight the importance of considering land uses as key factors influencing soil biota community and soil chemical traits. Thus, long-term experiments considering land uses (e.g., conventional farming system, fruticulture, and agroecological farming system) may exploit negative effects of land uses on soil biota abundance on the one hand, while positive effects on soil chemical traits on the other hand.
Keywords: Agroecological farming system; Conventional farming system; Fruticulture; Soil food web; Tropical Seasonal Dry Forest